Impaired Efflux of the Siderophore Enterobactin Induces Envelope Stress in Escherichia coli - Guest, Randi L.; Court, Emily A.; Waldon, Jayne L.; Schock, Kiersten A.; Raivio, Tracy L. (Frontiers in Microbiology, 2019)
The Cpx response is one of several envelope stress responses that monitor and maintain the integrity of the gram-negative bacterial envelope. While several conditions that are known or predicted to generate misfolded inner membrane proteins activate the Cpx response, the molecular nature of the Cpx inducing cue is not yet known. Studies have demonstrated that mutation of multidrug efflux pumps activates the Cpx response in many gram-negative bacteria. In Vibrio cholerae, pathway activation is due to accumulation of the catechol siderophore vibriobactin. However, the mechanism by which the Cpx response is activated by mutation of efflux pumps in Escherichia coli remains unknown. Here we show that inhibition of efflux by deletion of tolC, the outer membrane channel of several multidrug efflux pumps, activates the Cpx response in E. coli as a result of impaired efflux of the siderophore enterobactin. Enterobactin accumulation in the tolC mutant reduces activity of the NADH oxidation arm of the aerobic respiratory chain. However, NADH dehydrogenase I, NADH dehydrogenase II, and cytochrome bo3 do not contribute to Cpx pathway activation in the E. coli tolC mutant. We show that the Cpx response downregulates transcription of the enterobactin biosynthesis operon. These results suggest that the Cpx response promotes adaptation to envelope stress in enteric bacteria that are exposed to iron-limited environments, which are rich in envelope-damaging compounds and conditions.